Sustainable worm control practices in South America - Amarante, Alessandro F. T. (Elsevier B.V., 2014)
A high prevalence of nematodes, especially Haemonchus contortus and Trichostrongylus colubriformis, that exhibit multiple anthelmintics resistance has been reported in sheep in several South American countries. For this reason, the development of strategies that are less dependent on anthelmintic treatments is imperative for the prophylaxis of gastrointestinal nematode infections in small ruminants. Integrated grazing using cattle and sheep can be used for pasture decontamination with considerable reduction of H. contortus and T. colubnformis infective larvae after cattle grazing. Several breeds of sheep exhibit genetically related resistance against nematode infections, as is the case of crioulo, native or naturalised breeds of sheep. These breeds descend from livestock introduced by Portuguese and Spanish settlers and have been submitted to a long process of natural selection in various environmental conditions. In the South, the Crioula Lanada breed is more resistant to H. contortus than are Corriedale sheep. In tropical areas, where the minimum temperatures are usually higher than 20 degrees C, hair sheep flourish, especially the Santa Ines breed, which also display a higher level of resistance to nematode infections compared with certain breeds of European origin. However, Santa Ines sheep have inferior carcass quality compared with other commercial breeds. Recent studies showed that the crossbreeding of Santa Ines ewes with sires of breeds with high potential for growth and meat production, results in crossbred animals with high productivity and a satisfactory degree of resistance against nematode infections. Several studies have indicated that improvement in nutrition has a beneficial effect on the development of resistance in lambs that were naturally or artificially infected with nematodes. Therefore, supplementary feeding and breeding strategies to improve resistance to nematodes are feasible options in the effort to reduce dependence on anthelmintic drugs to control worm infections in sheep. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Haemonchus; Nematodes; Prophylaxis; Anthelmintics